2011
DOI: 10.1080/20780389.2011.625240
|View full text |Cite
|
Sign up to set email alerts
|

Living Conditions in Côte D'ivoire and Ghana, 1925–1985: What do Survey Data on Height Stature Tell Us?

Abstract: We find with survey data that the increase in height stature experienced by successive cohorts born in Côte d'Ivoire and Ghana during the late colonial period is almost as high as the increase observed in France and Great-Britain over the 1875-1975 period, even when correcting for the bias arising from old-age shrinking. In contrast, the early post-colonial period is characterized by stagnation or even reversion, not only in Côte d'Ivoire and Ghana but also in other countries in Western Africa. We argue that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The contribution of environmental conditions to these differences is illustrated, ironically, by inequality among Whites (Keegan 1987, 28-9;Phillips 1987). Unterhalter (1982, 631) Baten and Blum (2012) and Cogneau and Rouanet (2011).…”
Section: Military Personnel Records From World Wars One and Twomentioning
confidence: 98%
“…The contribution of environmental conditions to these differences is illustrated, ironically, by inequality among Whites (Keegan 1987, 28-9;Phillips 1987). Unterhalter (1982, 631) Baten and Blum (2012) and Cogneau and Rouanet (2011).…”
Section: Military Personnel Records From World Wars One and Twomentioning
confidence: 98%
“…We emphasize that these patterns are for women over the period 1961–1985. Over the period since 1920 there is evidence of substantial gains in male heights in several African countries (Moradi 2009, Cogneau and Rouanet 2009). …”
Section: Datamentioning
confidence: 99%
“…In Uganda, marriage registers of the Anglican Church Mission Society (CMS) are among the earliest written records documenting the vital history of native spouses for the entire colonial era, comprising brides' and grooms' self-reported age at first marriage, occupations, location of residence and literacy status (inferred from signatures), as well as their fathers' occupations. Thus, this case-study complements the recent wave of scholarship (e.g., Moradi 2009;Cogneau and Rouanet 2011;Austin et al 2012;Wantchekon et al 2013;Cogneau and Moradi 2014) that has demonstrated that case-studies using historical micro-data from Africa present a real alternative to broad-brushed 2 Hereafter the shorter term 'Africa' is used for 'sub-Saharan Africa'.…”
Section: Introductionmentioning
confidence: 88%